Planear la sostenibilidad en territorios de la interculturalidad: análisis de la política nacional de edificaciones sostenibles en Colombia desde la perspectiva del buen vivir (2020)
Since the 1960s, the world has created strategies to minimize the negative impact of the construction sector on natural resources and among the alternatives, sustainability as a concept stands out, which has set a trend in the sector. Sustainable or green buildings are alternatives that seek to improve the energy efficiency of the building, and thus minimize negative impacts of construction in the territory, in favor of a better quality of life for its inhabitants. Therefore, the public policy of sustainable buildings arises in Colombia, in response to these needs of the Colombian context. However, taking into account this as a fully intercultural context and with a complex diversity at the socio-spatial level, it is necessary to analyze this policy from a critical perspective, which not only transcends the closed reading from traditional development models, but also allows the recognition of other dimensions and paradigms of the topic. Therefore, this work proposes an analysis from the perspective of Good Living as another way of thinking about environmental protection and the care of biodiversity as multidimensional issues that cannot be separated from social dimensions, and that requires a participatory and active approach communities (Acosta, 2016). This perspective of integrating original visions of the South American peoples is proposed, coherent with the plural and intercultural reality of Colombia, as it is expected to explain in the body of the document. It begins by introducing the guiding elements of the analysis, such as the socially and academically relevant approach to the problem, the theoretical referents and prioritized antecedents; Subsequently, the methodological design that would give rise to the results and the specific analysis of the interest of this study focused on the aforementioned policy is presented.